(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Brain tumor classification is a difficult task for manual diagnosis system in the health care industry. The proposed paper has examined the artificial intelligence deep learning algorithms to perform the classification process. The process has been done by using Support Vector Machine algorithms and the same process has been done by using Artificial Neural Networks process. The training data is collected from hospitals and converted the MRI images into JPEG images and used in the comparison and classification of data. The paper has examined more than 4000 images to perform the classification using these two algorithms. The results were extracted and compared. The comparative results revealed that the classification process for brain tumor disease intensity with the distinct grades. The results were evaluated and found that the classification process done using the ANN has produced much better and faster results than SVM algorithms.